CLINICAL AND EPIDEMIOLOGICAL CHARACTERIZATION, ANESTHETIC-SURGICAL PROCEDURE, AND INTRAOPERATIVE PHARMACOLOGICAL MANAGEMENT: ELECTIVE CRANIOPLASTY - Dalla Maria, Lucas; Fiorentin, Jamerson; Kauer, Victor Luiz Ferreira; de Oliveira, Marcelo Augusto Landim Arteiro; Pagnussatt Neto, Eugenio; da Silva, Shana Ginar; Lindemann, Ivana Loraine (Seven Editora, 2026)
Elective cranioplasty is a complex neurosurgical procedure aimed at reconstructing cranial defects resulting from trauma, tumor resections, post-craniectomy syndromes, and other neurological conditions. Although planned, this intervention involves relevant physiological challenges, particularly regarding anesthetic management and the maintenance of hemodynamic stability, which are essential factors to ensure adequate cerebral perfusion and prevent perioperative complications. In light of the above, this study aims to describe the clinical-epidemiological profile, anesthetic-surgical act, and intraoperative pharmacological approach. This is a cross-sectional study conducted in a tertiary hospital, including patients who underwent elective cranioplasty between January 2020 and December 2022, whose data were collected from electronic medical records. In the sample (n = 53), the following characteristics were highlighted: female sex (58.5%), age equal to or greater than 60 years (34.0%), white skin color (100.0%), current or previous smoking (22.6%), current or previous alcohol consumption (54.7%), non-eutrophic patients (62.5%), with comorbidities (98.1%) and previous surgeries (84.9%). In the anesthetic-surgical act, surgical time between 241 and 320 minutes (37.7%), general anesthesia (100.0%), orotracheal intubation (100.0%), and dorsal decubitus (92.5%) were observed. The most commonly administered intraoperative medications were propofol, remifentanil, sevoflurane, intravenous lidocaine, cisatracurium, neostigmine, and levobupivacaine, and a high use of ondansetron, cefazolin, ephedrine, dexamethasone, mannitol, and metaraminol was also observed. Patients undergoing elective cranioplasty in the neurosurgery service in question are predominantly women, older adults, non-eutrophic, with comorbidities and previous surgeries, undergoing procedures in dorsal decubitus, with prolonged surgical time, general anesthesia, and orotracheal intubation. The proper integration of patient clinical characteristics, surgical technique, anesthetic management, and pharmacological approach in elective cranioplasties is essential to optimize perioperative care, in-hospital safety, and clinical prognosis.